The Influence of Teacher Communication Patterns in Aqidah Akhlak Education on Students' Academic Achievement - Mursal Aziz; Dedi Sahputra Napitupulu; Fadilani Azmi Parapat (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aimed to examine the effect of teacher communication patterns on student academic achievement in Aqidah Akhlak at MIS Islamiyah Londut, North Labuhanbatu. This quantitative correlational study involved 33 students who were selected through purposive sampling. Data were gathered through questionnaires, recordings, and classroom observations, with all instruments validated and tested for reliability. Data analysis employed simple linear regression, a t-test, and R² analysis to assess the relationship between teacher communication and student academic outcomes. The results revealed a significant impact of teacher communication patterns on student achievement. The t-count value (19.334) exceeded the t-table value (1.692), and the R-squared value (0.923) indicated that the communication patterns employed by teachers could explain 92.3% of the variance in student performance. These findings affirm that clear, engaging, and responsive communication in the classroom substantially enhances students' understanding and academic success. This study highlights the importance of effective teacher communication in promoting student learning, especially in values-based subjects like Aqidah Akhlak. It suggests that educators should adopt more interactive and student-centered communication strategies. Training programs and workshops focusing on pedagogical communication skills such as active listening, questioning techniques, and feedback strategies should be prioritized. Additionally, school leaders can incorporate communication quality as a key metric in evaluating teaching effectiveness. For teacher education institutions, these findings support the integration of communication-focused modules into pre-service and in-service teacher training to better equip educators for meaningful classroom interactions.